1993
DOI: 10.1007/bf01476292
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous Selective Cordotomy

Abstract: In this article the technique of CT-Guided Selective Cordotomy is described. The advantages of CT guidance in percutaneous cordotomy are the measurement of spinal cord diameters at the lesion site for each individual patient, direct visualization of target electrode relations, demonstration of spinal cord displacement during the procedure and localization of the electrode system in a specific part of the spinothalamic tract. Local destruction of the spinothalamic tract leads to selective cordotomy. Since 1987,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Technical advancements in imaging and radiofrequency (RF) ablation have led to the development of a minimally invasive percutaneous cervical cordotomy by Kanpolat et al [6] that can be safely performed under computerized tomography (CT) [6,7,8,9,10]. In the past year, we have started to perform percutaneous cervical cordotomies using the O-Arm (Medtronic Navigation Inc.).…”
Section: Introductionmentioning
confidence: 99%
“…Technical advancements in imaging and radiofrequency (RF) ablation have led to the development of a minimally invasive percutaneous cervical cordotomy by Kanpolat et al [6] that can be safely performed under computerized tomography (CT) [6,7,8,9,10]. In the past year, we have started to perform percutaneous cervical cordotomies using the O-Arm (Medtronic Navigation Inc.).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improvements in lesioning technique, the procedure was advanced through myelography to outline the spinal cord, electrical impedance monitoring of needle penetration, and the use of physiological confirmation of electrode position in awake patients [18,19,20,21,22,23,24,25,26]. Most recently, Kanpolat et al [7,15,27] introduced computed tomographic (CT)-guided percutaneous cordotomy, which has greatly enhanced the safety and efficacy of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of CT-guided PCC demonstrated that the application of advanced radiographic techniques could increase the precision of PCC [5]. However, CT guidance for PCC is often not utilized due to the cumbersome nature of the equipment and lack of availability of intraoperative CT scanners.…”
Section: Discussionmentioning
confidence: 99%
“…Since its original description in 1962, electrode placement has been based on the visualization of the dentate ligament using lateral intraoperative fluoroscopic myelography, CSF flow through the introducing needle, and changes in tissue impedance [1][2][3][4]. CT guidance has been the only significant advancement in PCC in the past quarter century [5].…”
Section: Introductionmentioning
confidence: 99%